In-school vaccination clinic at Fort Riley Middle School methods and evaluation - Webb, Megan (Kansas State University, 2011)
Capstone field experience project with the Fort Riley Department of Public Health (FRPH). This project was two-fold. The first part of the project was to observe, assist with, and develop an understanding of the different areas of the department of public health at Fort Riley. The second was to organize, manage, and analyze a vaccination clinic at the Fort Riley Middle School. The vaccination clinic offered vaccines for chicken pox, tetanus/diphtheria/pertussis, meningococcal disease, human papillomavirus, and the flu.
Keywords: Vaccination clinic; Chicken pox; Health promotion; Public health; Public Health (0573)